Les promenades de Paris de Charles-Adolphe Alphand - Chiara Santini (Projets de Paysage)
Les Promenades de Paris (1867-1873), a two-volume book led by French engineer of the Corps of Bridges and Roads C. A. Alphand, within the framework of the Haussmann Plan, represents an account of paramount importance in order to grasp the discourse on landscape planning in the 19th century and its circulation towards the public. In this text, which mentions the first results of a research on theoretical skills and know-how implied in the implementation of the project of Haussmannian open spaces, we shall offer an editorial history of the book and its narrative structure, as well as its originality within the wider framework of literature about gardens’ Art history (financing, circulation, address, conception).